Urban and Rural Public Trust to Government in Covid-19 Pandemic Responses - Khusnul Prasetyo; Rian Septrianto Maulana (Jurnal ILMU KOMUNIKASI, 2023)
This study attempts to assess the level of public trust in the Surabaya City Government and Banyuwangi Regency Government's handling of Covid-19. Utilizing a survey technique that was descriptively analyzed. Using the quota sampling method, up to 400 samples from each city/region's generation Y and Z were collected. According to the findings, there is a high level of trust in all dimensions of the Banyuwangi Regency Government. Medium levels of trust were accorded to the Surabaya City Government in terms of responsiveness and reliability, but high levels of trust were accorded in terms of integrity, transparency, and fairness.